Europe and Russia on the Balkan Front (ISPI Publications, 2023)
The war in Ukraine has taken its toll on the stability of the Balkans by reshuffling regional geopolitics and reviving diplomatic competition between the West and Russia. Since the summer of 2022, growing tensions between Kosovo and Serbia have raised concerns about a possible Russian involvement and pushed the European Union to react promptly. By brokering a new normalisation agreement, the West seeks to prevent new hotbeds in Europe and push Russia one step back from the Balkans. Meanwhile, the Russian invasion of Ukraine has given new momentum to the integration process of candidate states, making EU membership a tangible goal rather than an unattainable dream. Will the EU be able to stabilise the Balkans? Will Russia continue to exert its influence in the region? Are Belgrade and Pristina on the eve of a new phase in the normalisation process?